Why the Jesus as mother tradition undermines the symbolic argument against women's ordination - Hibshman, Grace ca. 20./21. Jh. (Religious studies, 2024)
The symbolic argument against women's ordination supposes that the theological significance of Christ's sex is his saving relationship to the Church, which takes the form of that of a bridegroom and his bride. It infers that a male priest alone is fit to represent Christ in his capacity as the Saviour of the Church, and thus that only men should be ordained. Since the emergence of the symbolic argument, however, scholars have rediscovered a long tradition of understanding Christ's saving relationship to the Church in maternal terms. While remaining neutral on whether women ultimately ought to be ordained or not, I argue that the kind of reasoning in the symbolic argument, if updated with the Jesus as Mother tradition, would suggest that it is fitting for a female priest to represent Jesus as Mother, just as it is fitting for a male priest to represent Christ the Bridegroom. Other critics of the symbolic argument tend to contest what is seen as its "literalist" or "essentialist" or overly gendered-valanced assumptions about priestly representation. I show that even if we grant to the symbolic argument more gendered and "essentialist" views on each of the major points of disagreement in these debates, women might still be fit to represent Christ because of the maternal ways that Christ has traditionally been thought to relate to the Church. As a result, the symbolic argument may be repurposed to support women's ordination rather than undermine it.